The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.26650/jecs2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Akademik Başarının Yordayıcıları: Sosyoekonomik Düzey ve Okul Türü

Abstract: We evaluated the effects of socioeconomic status and school type on academic achievement based on data from two million students over a 10 year period through three national transition systems in Turkey. Each of the three transition systems has its own national examination, and the data includes only students who took these exams. We used covariance analysis to compare the mean scores of public schools and private schools after controlling the effect of students' socioeconomic levels. We found that students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Students with low SES experience greater barriers in accessing resources. In a study with a Turkish sample, students' SES negatively impacted their academic achievementand these consequences persisted in later stages of life (Suna et al, 2020). In another study, Karaağaç Cingöz and Gür (2020) identified that Turkish students' SES affected their performance in national exams required to transfer from lower secondary school to upper secondary school at a greater degree than indicated in PISA surveys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students with low SES experience greater barriers in accessing resources. In a study with a Turkish sample, students' SES negatively impacted their academic achievementand these consequences persisted in later stages of life (Suna et al, 2020). In another study, Karaağaç Cingöz and Gür (2020) identified that Turkish students' SES affected their performance in national exams required to transfer from lower secondary school to upper secondary school at a greater degree than indicated in PISA surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Schools may help to compensate for the inequalities experienced by students from low socioeconomic backgrounds; however, they face an uphill battle in doing so. One study that followed two million students in Turkey over a 10-year period revealed that students with high SES attending private schools had higher academic achievement in mathematics, science and language, and that this difference persisted even when they were transferred to different types of high schools (Suna et al, 2020). This suggests that schools not only fail in making up for such inequalitiesthey also exacerbate them.…”
Section: Ses and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the intervention known as 'coefficient regulation', which restricts access of VET graduates to higher education, has lowered the perceived value of VET and accelerated its transformation into a type of education that high performing students no longer prefer. On the other hand, placement of students in all schools based on examination performance increased the clustering of low performing students in VET institutions (Suna, Tanberkan, Gür, Perc, & Ozer, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian terkait prestasi akademik telah banyak dilakukan di berbagai negara dengan segi pengaturan yang beragam seperti Cina (Liu et al, 2019), Turkey (Suna et al, 2020), dan Meksiko (Ibáñez et al, 2019). Kajian ilmiah terkait prestasi akademik di Indonesia pun telah dilakukan, seperti menganalisis hubungan student engagement dengan prestasi akademik, M-Score, orientasi motivasi berprestasi pada kesiapan akademik, serta kegiatan non-akademik berkaitan dengan prestasi akademik (Ocvitasari, 2020), dan motivasi berprestasi memiliki peranan sebagai moderator terhadap prestasi akademik mahasiswa sekaligus kecerdasan emosi (Marvianto et al, 2020).…”
Section: Pendahuluanunclassified